Science and technology in light of religion - Rolston, Holmes, 1932-2025, author; Baker Academic, publisher (Colorado State University. Libraries, 2009)
Despite evident progress in the sciences the value questions remain as acute as ever. Technical sciences such as medical and computer science raise both theoretical and ethical issues, because they make possible novel, sometimes quite unprecedented, human actions. There lie crises ahead, not for the lack of science, but for the lack of a wisdom that only religions can supply--worldviews that orient and redeem us.
Keywords: scientific method; theology; biology; physics; Christian West; evolutionary biology